Analisis Silistika Pada Puisi “Kau Ini Bagaimana Atau Aku Harus Bagaimana” Karya Gus Mus - Asep Maulana (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Literary work is a study of stylistics that uses literary language styles as a medium to discover its aesthetic value. Stylistics is the science of using language in literary works. The use of specific language styles in literary works created by the author himself. Therefore, the objective of this research analysis aims to determine the use of language styles (figure of speech), describe the diction and message to be conveyed in the poem